Inter-area transfer capability assessment considering optimal flexible solutions of capacity benefit margin - Muhammad Murtadha, Othman; Nurulazmi, Abd Rahman; Daw salleh, Sasi; Ismail, Musirin, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/